2004
DOI: 10.1002/acp.962
|View full text |Cite
|
Sign up to set email alerts
|

Smoking attenuates regular aerobic exercise benefits to episodic free recall immediately following strenuous physical activity

Abstract: The present study was designed to evaluate the extent to which free recall performance is influenced by competing demands on physiological resources dependent on blood-oxygen levels. Fifty-six healthy young adults (mean age ¼ 20 years) were allocated to groups (n 1-4 ¼ 14) according to their level of exercise (more than 6 h aerobic exercise per wk, or sedentary 1 ) and smoking (more than 10 cigarettes per day, or none) behaviour. Participants performed two free recall tasks, one under normal physically inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Although performance on the Stroop task has been shown to be reduced during nicotine abstinence (Gross et al, 1993), it may be that other aspects of information processing are more sensitive to influence during and following exercise. For example, other studies have found positive effects of a single session of exercise on working memory (Bunce et al, 2004;Churchill et al, 2002;Williams and Lord, 1997), and simple reaction time (Hogervorst et al, 1996). Also, Hall et al (2001) concluded that not all forms of executive control will respond in the same fashion to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Although performance on the Stroop task has been shown to be reduced during nicotine abstinence (Gross et al, 1993), it may be that other aspects of information processing are more sensitive to influence during and following exercise. For example, other studies have found positive effects of a single session of exercise on working memory (Bunce et al, 2004;Churchill et al, 2002;Williams and Lord, 1997), and simple reaction time (Hogervorst et al, 1996). Also, Hall et al (2001) concluded that not all forms of executive control will respond in the same fashion to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Also, two studies were not published [7,8] and two were published abstracts [9,10], but are considered in the review due to their unique methodology. Three additional studies were excluded from this review, as the focus was not on smoking‐related withdrawal symptoms or cravings [11] or did not examine the effect of single bouts of exercise [12,13].…”
Section: Methodsmentioning
confidence: 99%